FAKTOR BRAND AWARENESS DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPATU MEREK NIKE TIRUAN DI HOME INDUSTRY CIKUPA TANGERANG - Ismayudin Yuliyzar (Universitas Muhammadiyah Tangerang, 2017)
This study attempts to analyze the Brand Awareness Factor and PricePerception of Purchasing Decisions for Nike brand shoes at CikupaHome Industry Tangerang. The sample of this study was 75 customerrespondents from 300 customers. The method used is quantitativemethods. Primary data collection was obtained from questionnairecollection. The analysis technique used is multiple linear regressionanalysis using Vesri SPSS 22 software. The results show that the partialvariable of Brand Awareness (X1) is positively and significantly related tothe Purchase Decision (Y). Price Perception (X2) has a positive andsignificant effect on Purchasing Decisions (Y). Simultaneously the BrandAwareness variable (X1) and Price Perception (X2) considers positiveand significant towards the Purchasing Decision (Y).